The importance of multiple Z- plasty- assisted physical therapy in the treatment of Dupuytren’s contracture - Nader Gomaa Elmelegy; Dalia Nader (Journal of Orthopaedic Surgery and Research)
Abstract Background The palmar aponeurosis is extremely adherent to the skin above it. Many of the pre-tendinous coarse fibers enter the dermis at an angle, not just in the palmar creases but also throughout the palm. It’s difficult to distinguish whether Dupuytren’s illness starts in the skin’s dermis or the palmar aponeurosis since the skin adheres so closely to the palmar fascia. In this work, we have investigated the clinical and histological origins of Dupuytren’s disease, as well as its impact on the disease’s management. Methods A clinical prospective study was conducted on 47 patients, 42 males and 5 females, who presented with Dupuytren’s contracture in the hands (29 patients were bilateral and 18 one-sided), in the period between April 2012 and September 2020. Results Histologically, all our specimens showed chronic inflammatory skin lesions showing hyperkeratotic epidermal covering and dermal infiltration with aggregates of chronic inflammatory cells, mainly lymphocytes and plasma cells, proliferated vascular spaces, and fibrous stroma. Clinical satisfaction was excellent in 67(88.2%) hands, good in six (7.8%)hands, fair in three (4%) hands, and no poor results. Conclusions Dupuytren’s disease is a chronic inflammatory skin illness that can penetrate fascia, as we’ve proved histologically and surgically. For a considerable reduction in recurrence, the adhering skin and accompanying cord must be removed. Level of evidence IV – therapeutic study.